The Role of Motivation in Mediating Knowledge and Self-Efficacy on Entrepreneurial Intentions in Graduates of the Faculty of Economics, Batanghari University, Odd Semester, Academic Year 2023-2024 - Andri Yandi; Agus Hermawan; Naswan Suharsono (Dinasti International Journal of Management Science, 2023)
This study is to examine the impact of motivation, knowledge, and self-efficacy on entrepreneurial intents in graduates of Batanghari University's Faculty of Economics, Odd Semester, Academic Year 2023–2024. 130 students from Batanghari University's Faculty of Economics who had completed their final exams and planned to participate in graduation in the odd semester of the 2023–2024 academic year made up the study's population. A sample size of 98 was reached by using a 5% margin of error to the hypothesis devised by Slovin to calculate the size or number of samples in this research. Partial Least Square (PLS) data analysis and a quantitative approach using a survey method are used in this study. The findings of the study demonstrate that knowledge and self-efficacy, both directly and indirectly through motivation, have a favorable and significant impact on students' plans to start their own businesses, as does motivation itself. In spite of this, students still choose to hunt for employment after finishing their education rather than taking the risk of starting their own business because they are terrified of the hazards involved.